Mast cells in oral lichen planus and oral lichenoid lesions related to dental amalgam contact - Mariana Saturnino de NORONHA; Giovanna Ribeiro SOUTO; Fernanda Aragão FELIX; Lucas Guimarães ABREU; Maria Cássia Ferreira AGUIAR; Elismauro Francisco MENDONÇA; Ricardo Alves MESQUITA (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract The aim of this study was to analyze the expression of mast cell markers toluidine blue, c-kit, and tryptase and presence of mononuclear inflammatory cells in oral lichen planus (OLP) and oral lichenoid lesions related to dental amalgam. Nineteen specimens of OLP, OLLC, and healthy oral mucosa were selected. Mononuclear inflammatory cells were analyzed. Histochemical and immunohistochemical analyses were performed using toluidine blue, anti-c-kit and anti-tryptase reagents, and the results were quantified in areas A and B of connective tissue. Mast cells of all OLP and OLLC samples were positive for toluidine blue, c-kit, and tryptase. The density of toluidine blue+, c-kit+ and tryptase+ mast cells was higher in tissue with OLP and OLLC compared with healthy controls (p < 0.05). No difference was noted in mast cells density between OLP and OLLC (p > 0.05). The density of tryptase+ mast cells was higher in the subepithelial region (area A) than the region below it (Area B) in OLLC (p = 0.047). The mononuclear inflammatory cell density was higher in OLLC compared to OLP, but without statistical significance (p > 0.05). A positive statistical correlation was found between mononuclear immune cells and density of c-kit+ and tryptase+ mast cells in OLP (r = 0.943 and r = 0.886, respectively). Our data demonstrate that the etiopathogenesis process of OLP and OLLC modulates the expansion and degranulation of mast cells; mast cells density, however, was similar between OLP and OLLC. The distribution of mast cells appears to vary along the lamina propria.